2022
DOI: 10.1038/s41467-022-31219-1
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater discharge as a driver of methane emissions from Arctic lakes

Abstract: Lateral CH4 inputs to Arctic lakes through groundwater discharge could be substantial and constitute an important pathway that links CH4 production in thawing permafrost to atmospheric emissions via lakes. Yet, groundwater CH4 inputs and associated drivers are hitherto poorly constrained because their dynamics and spatial variability are largely unknown. Here, we unravel the important role and drivers of groundwater discharge for CH4 emissions from Arctic lakes. Spatial patterns across lakes suggest groundwate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…As a natural tracer of groundwater and a driver of CO 2 and CH 4 emission from coast and lake waters (Santos et al 2012, Olid et al 2022 Radon in SPout glacial lake which acted as CO 2 source was much larger than that of other glacial lakes (figure 2 suggesting the potential contribution from groundwater (with the 222 Radon of 2360 ± 555 Bq m −3 ) nearby SP glaciers. This phenomenon indicated groundwater input could alter GHG emissions from lake waters, which would be important in lake carbon budget as temperature rise is exacerbating groundwater inputs to lakes of the TP (Lei et al 2022).…”
Section: Glacial Lakes Of the Tp As Ch 4 Sources And Co 2 Sinksmentioning
confidence: 98%
“…As a natural tracer of groundwater and a driver of CO 2 and CH 4 emission from coast and lake waters (Santos et al 2012, Olid et al 2022 Radon in SPout glacial lake which acted as CO 2 source was much larger than that of other glacial lakes (figure 2 suggesting the potential contribution from groundwater (with the 222 Radon of 2360 ± 555 Bq m −3 ) nearby SP glaciers. This phenomenon indicated groundwater input could alter GHG emissions from lake waters, which would be important in lake carbon budget as temperature rise is exacerbating groundwater inputs to lakes of the TP (Lei et al 2022).…”
Section: Glacial Lakes Of the Tp As Ch 4 Sources And Co 2 Sinksmentioning
confidence: 98%
“…Nevertheless, lakes are highly heterogeneous across the globe (Guo et al, 2021), especially for those big lakes, such that regional lake simulation may introduce a high uncertainty. Furthermore, recent studies have found that groundwater discharge could be an important pathway as lateral CH 4 inputs to Arctic lakes that links CH 4 production in thawing permafrost to atmospheric emissions via lakes (Olid et al, 2022). Jammet et al (2015) also confirmed that spring is a crucial period for methane dynamics in sub-Arctic shallow lakes while large methane emissions were observed during the spring thaw.…”
Section: Uncertainty Analysis and Future Workmentioning
confidence: 67%
“…Furthermore, recent studies have found that groundwater discharge could be an important pathway 345 as lateral CH4 inputs to Arctic lakes that links CH4 production in thawing permafrost to atmospheric emissions via lakes (Olid et al, 2022). Jammet et al (2015) also confirmed that spring is a crucial period for methane dynamics in subarctic shallow lakes while large methane emissions were observed during the spring thaw.…”
Section: Uncertainty Analysis and Future Workmentioning
confidence: 69%